Russia and Poland: Problems of Inevitable Coexistence - D. V. Ofitserov-Belskiy (Vestnik MGIMO-Universiteta)
Over the last quarter of the century relations between Russia and Poland are balancing between trying to understand the burden of mutual guilt and a desire to construct non-emotional pragmatic relations. Sources of tension vary. In particular, it is the desire of Poland to position itself as a valued player in NATO and the EU and the role distance between the two countries in IR system, which does not allow Russia to maintain an equal political dialogue with Poland. In fact, Poland is not afraid of a direct threat from Russia, but the worst scenario is the one in which Russia without changing the content of its imperial policy can be accepted as a full partner in the international community. The evolution of Russian statehood and national specifics of democracy is largely determined the assessment of the prospects of Russian politics in Poland. The mistake of Polish diplomacy last years was that it took no direct efforts to improve relations with Russia, but only tried to impose the dialogue on Russian authorities. Diplomatic methods were designed to hurt Russian interests and to create a topic for discussion. In response, after 2006 Russia chose the tactic of ignoring Poland. But, ignoring Polish authorities, Russian politicians acted similarly with other political forces. In Poland among influential political forces, there was and there is still no loyalty to Russia. For Russian interests it is no matter who are or will be in power in Poland. However as a rule, it is an important factor that foreign policy decisions are de facto within the competences of the President and the government, as well as experiencing a significant influence of the parliamentary forces. Recent trends show no tangible innovations in bilateral programme. But innovations appear in multilateral and conflict enough issues, such as deployment of US missile defense system in Poland or Polish supervision of "Eastern Partnership" programme. The main problem is low self-sufficiency of bilateral relations and excessive influence of third countries. Any efforts to normalize bilateral relations will be meaningless until the weight of bilateral relations really increases to each of the party.